World Economic Outlook, October 1985 Revised Projections. (World Economic Outlook; World Economic Outlook ;, 1985)
This paper highlights that there have been increasing signs of hesitancy in the pace of world economic expansion in the first half of 1985. In the United States, output growth declined to an average of 1 percent (at an annual rate) in the first two quarters of the year from 5.7 percent during 1984, and in other industrial countries, the pace of recovery was also generally subdued. Commodity prices fell significantly, thus weakening growth prospects in many developing countries.